PENYELESAIAN CLEARANCE DENGAN SISTEM INAPORTNET GUNA MEMPERLANCAR ESTIMATED TIME DEPARTURE - Vega F. Andromeda; I Made Wahyu S. Putra (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2020)
Abstract There is still a delay time of up to 86% and utilization of the pier that has not been optimal causing inefficiency in ports in Indonesia. Idle time that occurs at the port is due to the slow processing of ships and goods documents. The implementation of the Inaportnet system is expected to accelerate clearance completion in an effort to expedite the Estimated Time of Departure. This research was conducted at PT Dharma Lautan Utama Tanjung Perak Surabaya Branch using a descriptive qualitative research method. The results showed that the process of completing ship clearance at PT Dharma Lautan Utama Surabaya Branch has changed using the online system or using the Inaportnet system, but this system is still constrained by inadequate internet connections. The number of vessel documents that must be completed, the checking system for expired date of ship certificates is still manual, the ups and downs, and the length of time waiting for the cargo to arrive at the port also causes the length of the clearance process at Tanjung Perak Port. Keywords: delay time; clearance; Inaportnet system; Estimated Time of Departure; ship. Abstrak Masih adanya delay time hingga 86% serta belum optimalnya utilisasi dermaga yang belum optimal menyebab-kan ketidakefisienan pelabuhan di Indonesia. Idle time yang terjadi di pelabuhan disebabkan karena waktu pengurusan dokumen kapal dan barang yang masih lambat. Penerapan sistem Inaportnet diharapkan dapat mempercepat penyelesaian clearance dalam upaya memperlancar Estimated Time of Departure. Penelitian ini dilaksanakan pada PT Dharma Lautan Utama Cabang Tanjung Perak Surabaya menggunakan metode penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa proses penyelesaian clearance kapal pada PT Dharma Lautan Utama Cabang Surabaya telah berubah menggunakan sistem online atau menggunakan sistem Inaportnet, tetapi sistem ini masih terkendala oleh koneksi internet yang kurang memadai. Banyaknya dokumen kapal yang harus diselesaikan, sistem pengecekan expired date sertifikat kapal masih manual, terjadinya pasang surut, dan lamanya menunggu muatan tiba pelabuhan juga menyebabkan lamanya proses clearance di Pelabuhan Tanjung Perak. Kata-kata kunci: delay time; clearance; sistem Inaportnet; Estimated Time of Departure; kapal.